2014
DOI: 10.1371/journal.pone.0094048
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic and Incidental Venous Thromboembolic Disease Are Both Associated with Mortality in Patients with Prostate Cancer

Abstract: IntroductionThe association between malignancy and venous thromboembolic disease (VTE) is well established. The independent impact of VTE, both symptomatic and incidental, on survival in patients with prostate cancer is not known. We conducted a retrospective cohort study to evaluate the effect of VTE of survival in prostate cancer.MethodsData regarding clinical characteristics, treatment and outcomes of 453 consecutive prostate cancer patients were collected. Fisher exact (categorical variables) and t-test (c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 33 publications
0
21
0
1
Order By: Relevance
“…28 Previous studies have documented a potential association between ADT and increased venous and arterial TE risk in PCa patients. 20,22,29 These studies, however, failed to explore the direct impact of ADT on coagulation and the independent role of disease burden.…”
Section: Discussionmentioning
confidence: 99%
“…28 Previous studies have documented a potential association between ADT and increased venous and arterial TE risk in PCa patients. 20,22,29 These studies, however, failed to explore the direct impact of ADT on coagulation and the independent role of disease burden.…”
Section: Discussionmentioning
confidence: 99%
“…Several retrospective studies in patients with cancer indicate that incidental PE can have important effects on survival, as well as on recurrent VTE [50,[59][60][61][62][63][64][65]. In one study that included a control group of patients without PE, matched for age, cancer histology and severity, the median survival in patients with incidental PE was 8 months, compared to 12 months for the matched controls [50].…”
Section: Relevance Of Incidental Pementioning
confidence: 99%
“…Several studies have also reported an association of VTE, both symptomatic and incidental, with poorer survival in patients with cancer. 3,4,[77][78][79] This may be a less important consideration in HSCT recipients, especially those maintained in remission. In the absence of studies that justify withholding anticoagulation in patients with incidental VTE, the 2012 ACCP guidelines recommend treating incidental VTE in a manner identical to symptomatic VTE with fulldose anticoagulation for at least 3-6 months, and longer in the presence of persistent or recurrent cancer.…”
Section: Incidental Vtementioning
confidence: 99%